The nhare mbira music trends in Zimbabwe since 1980 - Muranda, Richard (Routledge, 2022)
This research focuses on the trends in nhare mbira music in Zimbabwe since 1980, examined in its traditional and contemporary musical contexts. After 1980 nhare mbira began growing steadily in the popular music industry and it is thus, important to examine the impact of modern technology on the performance, preservation and production of nhare mbira. The controversies on the use of the traditional nhare mbira instrument in churches, education, social and political systems in Zimbabwe are also examined. The research reveals that nhare mbira is imbedded in most indigenous popular genres, and is commonly used at most musical events of the Shona-speaking people of Zimbabwe. The traditional dances shangara, katekwe, jiti, mbende, mhande and mbakumba are closely associated with nhare mbira. The findings reveal that there are two broad categories of nhare mbira genres – one being pasichigare, which is performed at traditional ceremonies and where the mbira players have a strict mandate to use traditional instruments only. The other genre is dandaro mbira, and this is mainly for entertainment and can be performed anywhere except at traditional ceremonies. Mbira dzeNharira and Mawungira eNharira ensembles, similar to western popular music bands, have electric nhare mbira instruments with built-in microphones like the electric guitars. Modern recording techniques have helped to record and preserve nhare mbira music since 1980. Radio and television (and even the internet) have done well in promoting nhare mbira music in different parts of the world. There are numerous websites with information on mbira music and the performers; however, the instrument is not embraced in the educational curriculum and modern churches in Zimbabwe.